2022
DOI: 10.3389/fneur.2022.922823
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between red blood cell distribution width at admission and post-stroke fatigue in the acute phase of acute ischemic stroke

Abstract: IntroductionPost-stroke fatigue (PSF) is a common complication in the patients with acute ischemic stroke (AIS). This prospective study aimed to investigate the relationship between red blood cell distribution width (RDW) at admission and PSF in the acute phase.MethodsThe AIS patients were enrolled in Nantong Third People's Hospital, consecutively. PSF in the acute phase was scored according to the Fatigue Severity Scale. Levels of RDW were measured at admission. The associations were analyzed using multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This is consistent with previous findings of abnormal rheological properties of red blood cells including higher shear stress, elongation, and elevation of RDW in GWI veterans [ 95 ]. An elevated RDW has been associated with fatigue in conditions such as systemic lupus erythematosus (SLE) [ 96 ] and post-stroke fatigue [ 97 ]. While the relation between RDW and fatigue is commonly related to iron deficiency and anemia [ 96 , 98 ], like in SLE we found no significant changes in hemoglobin (HGB) that would support this.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous findings of abnormal rheological properties of red blood cells including higher shear stress, elongation, and elevation of RDW in GWI veterans [ 95 ]. An elevated RDW has been associated with fatigue in conditions such as systemic lupus erythematosus (SLE) [ 96 ] and post-stroke fatigue [ 97 ]. While the relation between RDW and fatigue is commonly related to iron deficiency and anemia [ 96 , 98 ], like in SLE we found no significant changes in hemoglobin (HGB) that would support this.…”
Section: Discussionmentioning
confidence: 99%
“…RDW at admission is the independent associated factor in many acute diseases. Peng et al [24] found that after the adjustment for potential confounding factors, RDW at admission remained the independent associated factor with post-stroke fatigue in the acute phase. Cai et al [25] revealed that RDW �14.45% at admission was associated with 28-day mortality in patients with ARDS using cox regression analysis, while Kaplan-Meier analysis showed patients with RDW �14.45% had a significantly lower survival rate than those with RDW <14.45%.…”
Section: Plos Onementioning
confidence: 99%
“…RDW: red cell distribution width, AUC: areas under curve, CI: confidence interval, NPV: negative predictive value, PPV: positive predictive value, SOFA: sequential organ failure assessment, RDW T0: RDW value within the 24 h after ICU admission, RDW T1: RDW value at24 to 48 h after ICU admission, RDW changes: RDW T1 minus RDW T0 Adjusted for age, ethnicity, type of ICU at first hospitalization, ventilation time, vasopressor use, RRT, antibiotics use, AKI, temperature, RR, weight, FIO2, BUN, lactate, Cr, INR, chloride, PTT, and CCI.…”
mentioning
confidence: 99%
“…Recently, numerous studies have reported that a higher level of RDW was associated with adverse outcomes in patients with the first stroke [10][11][12][13][14]. For example, João Pinho et al [11] performed a single-center retrospective cohort study and found that patients in the higher quartiles of RDW presented a lower 1-year survival (p < 0.001).…”
Section: Introductionmentioning
confidence: 99%